2018
DOI: 10.1021/jacs.8b04786
|View full text |Cite
|
Sign up to set email alerts
|

Integrating Organic Lewis Acid and Redox Catalysis: The Phenalenyl Cation in Dual Role

Abstract: In recent years, merging different types of catalysis in a single pot has drawn considerable attention and these catalytic processes have mainly relied upon metals. However, development of a completely metal free approach integrating organic redox and organic Lewis acidic property into a single system has been missing in the current literature. This study establishes that a redox active phenalenyl cation can activate one of the substrates by single electron transfer process while the same can activate the othe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
53
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 48 publications
(54 citation statements)
references
References 47 publications
1
53
0
Order By: Relevance
“…We have previously observed that the redox active PLY can facilitate single electron transfer (SET) to a class of substrates 4244. In recent reports, we established that the reduced phenalenyl radical triggers a SET process to execute transition metal-free C–H functionalization 42,44. Since redox equivalents can be stored in 2 , we envisaged that similar SET could be augmented to accomplish reduction of carboxylic acids by silane.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We have previously observed that the redox active PLY can facilitate single electron transfer (SET) to a class of substrates 4244. In recent reports, we established that the reduced phenalenyl radical triggers a SET process to execute transition metal-free C–H functionalization 42,44. Since redox equivalents can be stored in 2 , we envisaged that similar SET could be augmented to accomplish reduction of carboxylic acids by silane.…”
Section: Resultsmentioning
confidence: 99%
“…This fact is fully consistent with a redox active PLY-ligand where the highly conjugated ligand backbone harbors the redox equivalent. We have previously observed that the redox active PLY can facilitate single electron transfer (SET) to a class of substrates 4244. In recent reports, we established that the reduced phenalenyl radical triggers a SET process to execute transition metal-free C–H functionalization 42,44.…”
Section: Resultsmentioning
confidence: 99%
“…It may be noted that the same NBMO of phenalenyl based molecules earlier played a key role in designing molecules with several intriguing properties such as organic magnets, conductors, organic spin based electronics, and batteries . Only recently, the use of phenalenyl‐based molecules has been evolving for the design of various catalysts . The topic of phenalenyl‐based molecules to design various catalysts and spin electronic materials was reviewed recently …”
Section: Methodsmentioning
confidence: 99%
“…[25][26][27][28][29][30][31][32][33][34] Only recently,t he use of phenalenyl-based molecules has been evolving for the design of variousc atalysts. [35][36][37] The topico fp henalenyl-based moleculest od esign variousc atalysts ands pin electronic materials was reviewed recently. [38] We initiatedt he present study by optimizing the reaction conditions for direct CÀHa rylation of thiophene( 2a)w ith para-chlorophenyl diazo-tetrafluoroborate salt (3a)u sing Fe(PLY-O,O) 3 (1)c atalyst (see the Supporting Information, Ta ble S1).…”
Section: Dedicatedtoprofessor Dietmar Stalke On the Occasion Of His 6mentioning
confidence: 99%
“…20 Recently, such in situ generated mono-reduced phenalenyl based radicals were reported in designing cathode materials for single component H 2 O 2 fuel cell 21 and in electron transfer catalysis during various organic transformations. [22][23][24][25] Such approach using in-situ generated mono-reduced phenalenyl radicals opens a possibility to bridge between two seemingly dissimilar areas such as spin-electronics and catalysis. 26…”
Section: Introductionmentioning
confidence: 99%